Additions to the millipede family Caseyidae Verhoeff, 1909. VI. Proposal of the new subfamily Opioninae, new species and records of the genus Opiona Chamberlin, 1951 and synonymy of Speyosia Causey, 1963 with Opiona (Diplopoda, Chordeumatida, Striariidea) - Shear, William A.; Marek, Paul E. (Zootaxa, 2026)
The caseyid millipede genus Opiona Chamberlin, 1951 contains 15 species distributed from southern Alaska and the Canadian province of British Columbia south to Santa Cruz County, California. We provide new records and range extensions of five previously described species and describe five new species: Opiona arcata sp. nov., O. johnsoni sp. nov., O. alsea sp. nov., O. triangalensis sp. nov., and O. laquesis sp. nov.. The following new synonym and combination are proposed: Opiona Chamberlin, 1951 = Speoseya Causey, 1963, syn. nov. and Opiona grahami (Causey, 1963) = Speoseya grahami Causey, 1963, comb. nov.—the valid names being the former. We propose a new subfamily Opioninae, subfam. nov., to include Opiona; Metopiona Gardner & Shelley, 1989; Opionoides Shear & Marek, 2025; Paropiona Shear & Marek 2025; and Benlomondia Shear & Marek, 2025.